Synthesis And Spectral Characterization Of Diphenylthiocarbazide For Use As A Selective Reagent In Spectrophotometric Metal Ion Detection - Nidhi, Nidhi; Pandey, Preeti (Journal of Neonatal Surgery, 2025)
Diphenylthiocarbazide (DPTC) is a sulfur- and nitrogen-containing organic ligand that holds significant potential as a selective analytical reagent for metal ion detection. In this study, DPTC was synthesized through a condensation reaction between phenyl isothiocyanate and hydrazine hydrate under controlled conditions. The synthesized compound was purified and structurally characterized using UV-Visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (1H NMR), elemental analysis (CHNS), and melting point determination. The presence of key functional groups including thiocarbonyl and aromatic amines confirmed the molecular integrity of DPTC. Spectral studies indicated that DPTC exhibits strong absorbance in the visible range, making it a suitable chromogenic reagent for colorimetric complexation with transition metal ions. Preliminary investigations demonstrated its high affinity and selectivity for copper(II) ions, forming a stable colored complex under mildly acidic to neutral pH conditions. The observed λmax and molar absorptivity values suggest that DPTC can serve as an effective ligand for spectrophotometric detection of trace metal ions. The results pave the way for further application of DPTC in environmental monitoring, pharmaceutical assays, and industrial quality control settings.